Impact of globalization on Islamic family values - Karim, Fatimah (Mission Soft Foundation, 2024)
Globalization, characterized by the rapid exchange of ideas, culture, and economic practices across borders, has significantly impacted various aspects of life, including family values. In the context of Islamic family values, globalization presents both challenges and opportunities. This article explores the impact of globalization on Islamic family values, examining the ways in which these traditional values are being influenced, preserved, or altered in the contemporary world.